Uji Biokompatibilitas Nanofiber Komposit Kitosan/PVA Sebagai Pembalut Luka - Abdul Supriyanto; Minarti Liana Murni; Fitri Marlina; Dwi Pangga (Lensa: Jurnal Kependidikan Fisika, 2018)
[Title: Chitosan/PVA Composite Nanofiber Biocompatibility Test as a Wound Wrap]. This study aims to make chitosan-based nanofiber from NTB local crab shells. The manufacture of nonofiber is intended for application in the medical world as wound dressing. Wound dressing was developed from the basic ingredients of chitosan from NTB local crab shells. This research was conducted using the electrospining method, namely by making fibers from nano-sized chitosan. The resulting wound dressing was analyzed using FTIR. The results of this analysis show that chitosan has an area of absorption or transmittance in some chitosan groups so that it shows a positive alloy on chitosan and PVA as antibacterial in wound dressing.